NUTRITIONAL SCREENING OF ELDERLY PEOPLE AFTER ISCHEMIC CEREBRAL VASCULAR ACCIDENT - de Sousa Nascimento Almeida, Alane (2024)
Apply the nutritional risk screening / nutritional mini-assessment in elderly patients affected by Cerebral Vascular Accident in a Public Hospital in the Sertão Central do Ceará. Cross-sectional study through field research of an exploratory nature, with a quantitative approach, through the application of the nutritional screening questionnaire Mini Nutritional Assessment (MNA) in hospitalized elderly people affected by stroke. The research was carried out with 103 patients, of which 45.6% (n 47) were women and 54.4% (n 56) men. The average age of the group was 73.62 years. The results of the MNA risk screening revealed that 60.2% of the elderly were at risk of malnutrition, 24.3% were eutrophic and 15.5% were malnourished. Although many individuals in this study are elderly with a nutritional status of eutrophy, overweight or obesity, these present alert factors for imminent nutritional risk.